Incorporating Choice: Examining the Beliefs and Practices of Behavior Analysts Working with Individuals with Disabilities - Veverka, Yev; Luna, Adriana; Penney, Ashley; Bateman, Katherine; Pritchett, Malika; Schwartz, Ilene; Zaino, Zeyad (Journal of developmental and physical disabilities, 2025)
Choice-making for individuals with disabilities is an important topic in the field of Applied Behavior Analysis (ABA). Choice is a fundamental human right, and opportunities to make decisions about an individual's own life honors and respects dignity and autonomy. This study explores the beliefs and practices of behavior analysts in relation to choice-making for individuals with disabilities. A total of 81 practicing behavior analysts participated in an online survey that assessed their training experience, beliefs about choice, and reported practices regarding choice in ABA service delivery. The survey responses were analyzed using descriptive statistics and Wilcoxon Signed-Rank Test to compare beliefs and practices. Results showed that while most behavior analysts strongly agreed that choice should be incorporated into ABA services, discrepancies were observed between beliefs and actual practice regarding various factors that influence opportunities to make choices. Multiple barriers to providing choice-making opportunities were identified. The findings underscore the need for increased training and coursework on the subject of choice as well as changes in practice.